2021
DOI: 10.3390/app11209503
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nutritional Habits and Moderate Red Wine Consumption in PON1 Status in Healthy Population

Abstract: Paraoxonase 1 (PON1) plays a role as antioxidant on HDL. Including in diet additionally ingest of polyphenolic compounds can stimulate PON1 transcription and increase its activity. The aim of this study was to evaluate the effect of dietary intake, red wine consumption, and PON1 genotypes (Q192R, L55M and C-108T) on the specific activity of PON1 in a healthy population. A descriptive and analytical pilot study was conducted in Mexican volunteers clinically healthy (n = 45) aged from 21–59 years. Over 6 weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…Paraoxonase 1 is a hydrolytic enzyme that contributes to the protective functions of high-density lipoprotein. A moderate intake of red wine was found to positively alter paraoxonase 1 activity in a healthy Mexican population [89]. A group of researchers [90] looked at the phenomenon of subclinical coronary atherosclerosis.…”
Section: Resveratrol In Cardiovascular Healthmentioning
confidence: 99%
“…Paraoxonase 1 is a hydrolytic enzyme that contributes to the protective functions of high-density lipoprotein. A moderate intake of red wine was found to positively alter paraoxonase 1 activity in a healthy Mexican population [89]. A group of researchers [90] looked at the phenomenon of subclinical coronary atherosclerosis.…”
Section: Resveratrol In Cardiovascular Healthmentioning
confidence: 99%
“…Although vitamin E is an acknowledged antioxidant, the studies failed to connect this beneficial effect to an increase in PON1 activity. Navarro-García et al [142] reported that the AREase activity of PON1 decreased as a result of tocopherol consumption. Similarly, another study with healthy volunteers supplemented with 4100 IU of α-tocopherol has shown a drop in the AREase activity of PON1 associated with HDL 2 and HDL 3 for about 15% [143].…”
Section: Vitamins and Trace Elementsmentioning
confidence: 99%
“…Studies focused also on the influence of B-vitamins on PON1 activity, but the results are contradictory. Navarro-García et al [142] found that vitamins B1, B2 and B6 decrease PON1 POase activity, while different groups reported an increase in POase and AREase activity caused by vitamin B6 in diabetic rats [147]. Manolescu et al [148] investigated the influence of the nutritional supplement ALAnerv ® containing B-vitamins and several minerals, such as selenium or calcium, with the addition of w-6 polyunsaturated fatty acids in a small group of post-acute patients.…”
Section: Vitamins and Trace Elementsmentioning
confidence: 99%
“…Yerba mate concludes various classes of chemical compounds, including caffeoyl derivatives (caffeic acid, chlorogenic acid, 3,4-dicaffeoylquinic acid, 3,5-dicaffeoylquinic acid, and 4,5-dicaffeoylquinic acid); flavonoids (catechins, quercetin, kaempferol, and rutin); vitamin B2, B1, and C; amino acids; and minerals (phosphate, iron, and calcium) [ 86 ]. In vitro studies have demonstrated that Ilex paraguariensis extract (2–20 microL/mL) provided concentration- and time-dependent protection against AAPH-induced HDL oxidation, maintaining PON1 activity and apoA-1 structure [ 47 ] ( Table 2 ). Moreover, an in vivo study demonstrated an increased plasma PON1 activity (about 10%) in healthy volunteers who received 0.5 L of Ilex paraguariensis extract compared to subjects who received 0.5 L of milk and coffee [ 49 ] ( Table 3 ).…”
Section: Effect Of Phytochemicals and Medicinal Plants On Paraoxonase...mentioning
confidence: 99%
“…Neither PON1 genotypes nor dietary intake impacted PON1 activity. Nevertheless, an increase in AREase activity of PON1 was observed in participants after wine consumption [ 47 ] ( Table 3 ). Kiyici et al reported that grape seed extract (GSE) administration was able to increase PON1 activities in streptozotocin-induced diabetic rats [ 39 ] ( Table 2 ).…”
Section: Effect Of Phytochemicals and Medicinal Plants On Paraoxonase...mentioning
confidence: 99%